2021
DOI: 10.3389/fphys.2020.620736
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Limitation in Children and Adolescents With Severe Refractory Asthma: A Lack of Asthma Control?

Abstract: BackgroundPatients with severe refractory asthma (SRA), even when using high doses of multiple controller medications in a regular and appropriate way, can have persistent complaints of exercise limitation.MethodsThis was a cross-sectional study involving patients with SRA (treated with ≥ 800 μg of budesonide or equivalent, with ≥ 80% adherence, appropriate inhaler technique, and comorbidities treated), who presented no signs of a lack of asthma control other than exercise limitation. We also evaluated healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 35 publications
3
6
1
Order By: Relevance
“…Indeed, 60.7% of our children with asthma who were categorized as inactive were also physically deconditioned, while all children with asthma and physical deconditioning were inactive. To our knowledge, only one other study has explored the underlying mechanisms of reduced exercise capacity in children with asthma by means of CPET; 15 that study focused on subjects with severe refractory asthma and reached conclusions similar to ours regarding the contribution of physical deconditioning. Of note, maximal incremental CPET has been shown to be the only reliable method to systematically assess the underlying etiology of reduced exercise capacity.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Indeed, 60.7% of our children with asthma who were categorized as inactive were also physically deconditioned, while all children with asthma and physical deconditioning were inactive. To our knowledge, only one other study has explored the underlying mechanisms of reduced exercise capacity in children with asthma by means of CPET; 15 that study focused on subjects with severe refractory asthma and reached conclusions similar to ours regarding the contribution of physical deconditioning. Of note, maximal incremental CPET has been shown to be the only reliable method to systematically assess the underlying etiology of reduced exercise capacity.…”
Section: Discussionsupporting
confidence: 77%
“… 13 , 14 A recent case-control study confirmed that children with severe refractory asthma may be less tolerant to exercise. 15 Using a CPET protocol similar to ours, the investigators also showed that EIB (documented in 30% of cases), physical deconditioning (25% of cases), and a combination of the two (25% of cases) could explain the reduced exercise capacity in that cohort. 15 Similar studies in adults have yield contradictory results.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations